PENERAPAN SISTEM INFORMASI POSYANDU BAGI KADER DI KECAMATAN SEMARANG SELATAN - Supriyanto, Aji; Hartono, Budi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Implementation of IbM is intended to develop Posyandu Information System (SiPosy- andu) which can be utilized for Posyandu cadres in Kelurahan Peterongan (Mitra1) and Pleburan (Mitra2) Kecamatan Semarang Selatan. IbM’s goal is the development, installation, implementa- tion of Siposyandu and Training for Posyandu cadres of sub-district, urban village and RT / RW in Semarang Selatan Semarang City. In order for the administrative system of recording, processing and reporting of posyandu that has been done manually can be developed into a basis of automated information system that provides accurate, detail, quick, easy, continuous, standard, and integrated information. Initial identification results indicate that the existing Posyandu system at the sub-dis- trict and sub-district levels only recruits the number of children under five and pregnant women, rather than identifying data on toddlers and pregnant women themselves as well as their health care measures. So the existing information is not based on a database that can show the identity of tod- dlers and pregnant women and health care record record in Posyandu. Therefore this SiPosyandu development will overcome the existing problems. The developed system is able to provide information on the identity of toddlers, pregnant women and health care history including nutrition and vitamins in Posyandu by cadres. So that the information provided more akuran based on row data formed in databse posyandu that processed correctly at the level of Posyandu. The method used is a review of participative actions in the form of identification of problems in the field, development and application of systems, and training of cadres for SiPosyandu operations. The products gener- ated from IbM are the installation and implementation of SiPosyandu on local server computer Posyandu cadres and web servers, as well as training for skilled cadres to operate the system